Inhibition of Olanzapine-Induced Weight Gain by the Retinoid Analog AM-80 - Richards, M.; Chiba, S.; Ninomiya, M.; Wakabayasi, C.; Kunugi, H. (Pharmacopsychiatry, 2013)
Weight gain and metabolic abnormalities are common side effects of antipsychotic treatment. Retinoids have been suggested as promising substances to suppress obesity. This study has investigated the effects of a retinoid agonist AM-80 on olanzapine-induced weight gain and metabolic changes in rats.Female Sprague-Dawley rats (7 weeks) were treated with AM-80 (1 mg/kg/day, subcutaneously) and/or olanzapine (4 mg/kg/day, intraperitoneally) for 21 days. Body weight and food/water intake were measured daily. The open field (OFT) and prepulse inhibition (PPI) tests were done on days 18 and 21, respectively. Animals were sacrificed on day 22 to measure weight of adipose tissues and serum levels of adiponectin and leptin levels.Olanzapine significantly increased body weight, food/water intake and the mass of inguinal adipose tissue (IAT) compared to vehicle-treated rats. AM-80 demonstrated significant inhibition of weight gain. No significant effect of olanzapine or AM-80 was found on behaviors or serum adiponectin/leptin levels.These findings suggests that AM-80 is a potential therapeutic agent to attenuate weight gain and metabolic side effects associated with olanzapine.
Keywords: olanzapine; obesity; metabolic syndrome; AM-80; retinoid